ANALISIS CEMARAN MIKROBIOLOGI BEBERAPA ASPEK PRODUKSI PADA PEDAGANG PENYEDIA MAKANAN DI SEKITAR KAMPUS UNIVERSITAS BUMIGORA MATARAM - NI WAYAN PUTU MEIKAPASA; THERESIA SUZANNA CATHARINA; LALU DANU PRIMA ARZANI (Universitas Mahasaraswati K. Mataram, 2023)
Most health problems by food are caused by contamination of microorganisms. This contamination can due because cleanliness or improper implementation of sanitation and hygiene. The aim of this research is to identify microorganism contamination in the production aspects of food traders around the Campus of Bumigora University Mataram. Total microbial testing was carried out using the Total Plate Count (TPC) method for air, table, floor, equipment and water samples. Another method for testing coliforms in water use the principle of the Most Probably Number (MPN) method. The observation results show that the environmental quality as seen from the total microbes in the air is below the threshold, namely <700 col/m3, so it is said to be still safe. Meanwhile, table, floor and equipment samples showed that the total number of microbes was high enough to exceed the required threshold, especially those related to eating utensils such as plates, glasses and spoons. The total microbial test in the water sources used by the three traders showed that the two water sources used contained microbial colonies which were tested via TPC with colony numbers ranging from 87.7 – 99 x 10-5 CFU/ml. The results of the coliform estimation test using the MPN method principle showed that there was no suspicion of any coliform bacteria contamination in the two water samples, which indicated that both water sources also met the clean water requirements according to Minister of Health Regulation No. 492 of 2010.